2014
DOI: 10.1093/mp/ssu018
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall, Cytoskeleton, and Cell Expansion in Higher Plants

Abstract: To accommodate two seemingly contradictory biological roles in plant physiology, providing both the rigid structural support of plant cells and the adjustable elasticity needed for cell expansion, the composition of the plant cell wall has evolved to become an intricate network of cellulosic, hemicellulosic, and pectic polysaccharides and protein. Due to its complexity, many aspects of the cell wall influence plant cell expansion, and many new and insightful observations and technologies are forthcoming. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(118 citation statements)
references
References 150 publications
2
109
0
Order By: Relevance
“…Nematode efectors including expansin, β-1,4-endoglucanase and polygalacturonase are released during primary infection and feeding site development. In plants, expansin proteins are secreted during growth processes to allow for cell enlargement [66]. Nematodes are believed to cause diferential expressions of plant genes encoding cell wall modifying proteins including expansins [67] quite possibly to mimic endogenous expansin production during feeding site development.…”
Section: Nematode Parasitism Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nematode efectors including expansin, β-1,4-endoglucanase and polygalacturonase are released during primary infection and feeding site development. In plants, expansin proteins are secreted during growth processes to allow for cell enlargement [66]. Nematodes are believed to cause diferential expressions of plant genes encoding cell wall modifying proteins including expansins [67] quite possibly to mimic endogenous expansin production during feeding site development.…”
Section: Nematode Parasitism Genesmentioning
confidence: 99%
“…Rme1 is considered a potential component of the Mi-1-mediated signaling pathway as studies have indicated tomato Rme1 mutants lack resistance to nematodes and whitelies [66]. Molecular changes in Rme1 protein conformation due to the presence of pathogens, may be recognized by Mi-1.1 which signals the hypersensitive response in the "guard hypothesis" [83].…”
Section: Mi-12 (Referred To Asmentioning
confidence: 99%
“…Bacteria produce cell wall lipopolysaccharides which are recognized by a surface-localized lectin S-domain receptor kinase (Macho and Zipfel, 2015). Fungi produce cell wall chitins that are recognized by a lysine motif (lysM) domain containing the RLK1 gene, the chitin elicitor receptor kinase (CERK1) in Arabidopsis and rice, which in turn regulates TFs that regulate R RRM genes to biosynthesize RRMs that reinforce cell walls (Bashline et al, 2014;Macho and Zipfel, 2015;Miya et al, 2007) (Figure 1). Necrotrophs and hemibiotrophs, and at advanced stages of infection the biotrophs, produce several enzymes (elicitors), such as cutinases, xylanase, cellulases, pectin lyases, and laccases to break down the host cell wall, which releases DAMP (plant signal molecules) (Boller and Felix, 2009;Pendleton et al, 2014).…”
Section: A Plant Receptor (Elrr and Err) Genes And Regulation Of Dowmentioning
confidence: 99%
“…The pathogens also try to neutralize the effect of these phytoalexins by converting them to less toxic oxidized forms or conjugate with glycosides through production of enzymes (Jeandet et al, 2014). Primary cell walls produced by cellulose and pectins are constitutively enforced by the deposition of secondary metabolites (RRC) (Bashline et al, 2014;Eudes et al, 2014;Nakano et al, 2015). In addition, following pathogen invasion, more secondary metabolites are induced (RRI) and these form complex polymers that are deposited in xylem vessels to enforce cell walls (Gunnaiah et al, 2012;Wang et al, 2014b;Yogendra et al, 2015a).…”
Section: B Resistance-related Metabolites (Rrm) and The Mechanisms Omentioning
confidence: 99%
“…It can allow cells to resist to compression forces [16]. Cell wall composition includes cellulose, hemicelluloses, pectins, proteins [17] and lignin in some cell types [18].Cellulose is a cell wall polysaccharide with a high molecular mass, formed by long linear chains of β-1,4-linked glucose residues forming microibrils [1 ]. Primary walls contain around 20-30% cellulose, and secondary walls up to 50% [20].…”
mentioning
confidence: 99%